2019
DOI: 10.1029/2018jc014871
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Water Levels for Australian Beaches Using Empirical Equations for Shoreline Wave Setup

Abstract: Empirical equations for wave breaking and wave setup are compared with archived shoreline wave setup measurements to investigate the contribution of wind waves to extreme Mean Total Water Levels (MTWL, the mean height of the shoreline), for natural beaches exposed to open ocean wind waves. A broad range of formulations is compared through linear regression and quantile regression analysis of the highest measured values. Shoreline wave setup equations are selected based on the availability of local beach slope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 45 publications
6
41
0
Order By: Relevance
“…Finally, the qn‐SSJPM does not consider the impact of wave processes on flood hazard and is therefore most suitable for wave‐sheltered harbors and embayments. During flood events, wave set‐up elevates the time‐averaged water level, and wave run‐up periodically further raises water level (O'Grady et al, 2019; Stockdon et al, 2006). These processes must be included for hazard analyses to be reliable at wave‐exposed coastlines; e.g., Lambert et al (2020) demonstrate that neglecting waves can lead to overestimating the time it will take for SLR to double the frequency of a given extreme water level.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the qn‐SSJPM does not consider the impact of wave processes on flood hazard and is therefore most suitable for wave‐sheltered harbors and embayments. During flood events, wave set‐up elevates the time‐averaged water level, and wave run‐up periodically further raises water level (O'Grady et al, 2019; Stockdon et al, 2006). These processes must be included for hazard analyses to be reliable at wave‐exposed coastlines; e.g., Lambert et al (2020) demonstrate that neglecting waves can lead to overestimating the time it will take for SLR to double the frequency of a given extreme water level.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of empirical formulae exist to estimate wave setup and runup. Recent studies have extensively tested the most commonly used ones (e.g., Atkinson et al, 2017; Cohn & Ruggiero, 2016; Di Luccio et al, 2018; Díaz‐Sánchez et al, 2014; Ji et al, 2018; O'Grady et al, 2019; Passarella et al, 2018; Power et al, 2019; Pullen et al, 2007; Sénéchal et al, 2011; Stockdon et al, 2014; Vousdoukas et al, 2012). These studies have shown the significant skills of these formulae in different study cases and their ability to outperform process‐based models for R 2% (Stockdon et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…An exception is the study of Gainza et al (2018) in which an interannual time series of wave runup was produced using a metamodeling approach. A complicating factor in studying low‐frequency changes in wave setup and runup is also their sensitivity to poorly known time‐varying local morphology (e.g., O'Grady et al, 2019). Yet, several studies have shown interannual variability of deep water wave energy flux, nearshore profile, shoreline position, and beach width and volume (e.g., Harley et al, 2017; Karunarathna et al, 2016; Kuriyama et al, 2012; Norcross et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, very few have quanti ed the physical drivers in a way that facilitates national or regional warning and monitoring for these hazards. This is likely due to signi cant gaps in driver and impact data (Greenslade et al 2020) and the complexity in calculating important local scale characteristics, such as nearshore wave transformations (O'Grady et al 2019a). This is further made complex by changes in the total water level, including GMSL and ESL, not occurring homogeneously around the world's coastlines due to variability in the natural system (Kirezci et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we have decided to use sea level observations and residual data for Portland for both study locations as it is likely more representative of the broader astronomical forcing and less likely to be heavily in uenced by local factors.The daily maximum residuals (the non-tidal component of the observed sea level) are very highly correlated between Portland, Stony Point and Lorne, the three ABSLMP sites in Victoria. Residuals are commonly-used metrics to identify storm surges, the physical phenomenon typically associated with high still water levels that lead to coastal impacts inVictoria (McInnes et al 2016;O'Grady et al 2019a). Pair-wise correlations (using Pearson's R) of 0.86 (Portland-Stony Point), 0.93 (Portland-Lorne) and 0.96 (Lorne-Stony Point) were calculated using data over the 2013-2019 (inclusive) period.…”
mentioning
confidence: 99%